2016
DOI: 10.1186/s12906-016-1303-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the sexual functions and NF-κB and Nrf2 pathways of some aphrodisiac herbal extracts in male rats

Abstract: BackgroundMucuna pruriens, Tribulus terrestris and Ashwagandha (Withania somnifera) are widely known as antioxidant effective herbals and have been reported to possess aphrodisiac activities in traditional usages. In this study, we determined the effects of these herbals on sexual functions, serum biochemical parameters, oxidative stress and levels of NF-κB, Nrf2, and HO-1 in reproductive tissues.MethodsThirty-five male rats were divided into five groups: the control group, sildenafil-treated group (5 mg/kg/d)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 45 publications
4
30
0
6
Order By: Relevance
“…The results indicated that the extract of TT was comparatively more potent than the two others. These herbs are potent enhancers of sexual function and behaviour by increasing the testosterone levels and regulating the NF-κB and Nrf2/HO–1 pathways in male rats [53]. …”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…The results indicated that the extract of TT was comparatively more potent than the two others. These herbs are potent enhancers of sexual function and behaviour by increasing the testosterone levels and regulating the NF-κB and Nrf2/HO–1 pathways in male rats [53]. …”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…ROS is the main cause of oxidative stress, which is thought to be an important and reasonable cause of idiopathic male infertility and sexual dysfunction, and oxidative stress-induced sperm DNA damage negatively affects the reproductive outcome [ 12 ]. In a previous study where we used Tribulus , Ashwagandha, and Mucuna separately in rats, we determined that their extracts may be potent enhancers for sexual function and behavior via increasing testosterone levels and regulation of NF- κ B and Nrf2/HO-1 pathway with a concomitant decrease in ROS levels as well [ 13 ]. Despite the fact that the small amount of ROS is required for healthy sperm functioning, excessive exposure to ROS levels can adversely affect spermatozoa quality and weaken overall fertilization capacity as well [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aphrodisiac-effective many plants and their extracts such as Epimedii herba (horny goat weed), Lepidium meyenii (Maca), Mucuna pruriens, Panax ginseng, Tribulus terrestris, and Withania somnifera (Ashwagandha) have been reported in the literature to increase sperm number, sexual strength, and testosterone levels while mostly lowering the detriments caused by oxidative stress in the metabolism as well when used at appropriate doses [ 13 , 21 ]. Thus, Mucuna pruriens , Tribulus terrestris , and Ashwagandha are aphrodisiac plants used for centuries in traditional Indian and Chinese medicine, which was shown to improve penile erection, develop sperm quality, enhance sexual behaviors, and increase androgen hormone levels in several studies [ 22 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproducibility and device/method sensitivity of LABGEOPT10 were established according to IVR-PT06 guidelines. Serum and liver MDA levels were measured using the method described by Sahin et al (16). Malondialdehyde (MDA) levels were measured using the fully automatic high-performance liquid chromatography (Shimadzu, Kyoto, Japan) equipped with a pump (LC-20 AD), an ultraviolet-visible detector (SPD-20A), an inertsil ODS-3 C18 column (250 × 4.6 mm, 5 m), a column oven (CTO-10ASVP), an autosampler (SIL-20A), a degasser unit (DGU-20A5) and a computer system with LC solution Software (Shimadzu) (16).…”
Section: Laboratory Analysismentioning
confidence: 99%